LOGIQUES DE SLOGANS PUBLICITAIRES SUR LES PRODUITS DE TABACS : POUR UNE PUBLICITE A CONTROVERSE INCLUSIVE - Irafiala, Toure (European Scientific Journal, ESJ, 2015)
Inclusive controversy advertising reconciles different motivations in the act of tobacco products consumption and opens another form of consumer communication. It operates on a conciliatory equation artifice slogans issued by promoters / industrial, society and consumers. The ethics of consumption assumed to result from the confrontation between incentives and disincentives slogans implicitly in the service of business ethics and business because it lays bare the sociological paradigms that underpin it. Advertising on inclusive controversial tobacco products enriches the paradigmatic field of commercial communication and mass consumption.